Effect of Centella asiatica as feed additive on blood profile, egg quality and gut microbial contents of ISA brown laying birds - Ajibade, Olabisi; Tayo, Grace Oluwatoyin; Olumide, Martha Dupe; Akintunde, Adeyinka Oye (Aceh Journal of Animal Science, 2023)
The use of medicinal plants is gaining popularity all over the world; hence there is a need to exploit various plants that could be of economic importance to animal. This study was conducted to investigate the utilization ofCentella asiaticaleaf meal (CALM) as feed additive in layers production. The study was carried out in two phases, the grower phase and layer phase. A total number of 150 birds were used at 10 birds per replicate of 3 replicates per treatments of a total of 5 treatments. The diets contained CALM at five levels of inclusion 0.0 % (control), 0.2%, 0.4%, 0.6% and 0.8% at grower and layer phases. The experiment was arranged in a completely randomized design layout. Hence, CALM showed potentials of being natural growth promoting additive. CALM used as additive at 0.2-0.8% inclusion level significantly increased (p0.05) final live weight, weight gain and improved feed conversion ratio at grower and layer phases. 0.6% inclusion of CALM increased packed cell volume (PCV) and haemoglobin (Hb) and 0.8% inclusion of CALM increased red blood cell (RBC) values at grower phase.At layer phase, 0.6% inclusion of CALM significantly increased (p0.05) PCV and RBC while 0.8% CALM significantly increased (p0.05) haemoglobin (Hb) value but there was significant reduction (p0.05) in total bacteria count (TBC) at the caecum and ileum of birds at grower and layer phases respectively.0.8% CALM inclusion resulted in significantly highest (p0.05) weight of eggs, hen day egg production at 4th, 8th and 12th week in lay. 0.6% inclusion of CALM significantly improved (p0.05) egg weight and yolk weight score at 12th weeks in lay. It can be concluded that the inclusion of CALM in the diets of Isa Brown birds, resulted in better blood profile, haematological and serum biochemical parameters, gut microbial population, egg production and quality of laying hens